1997
DOI: 10.1136/jnnp.62.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Motor and cognitive function in Lewy body dementia: comparison with Alzheimer's and Parkinson's diseases.

Abstract: Objective-Motor and cognitive function were compared in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
137
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 39 publications
14
137
2
2
Order By: Relevance
“…Some studies report PDD to be more impaired, 6,7 whereas other studies found no differences. 8,9 Similar inconsistencies have been found when perception of PD patients was compared with healthy controls.…”
Section: Abstract-objectivesupporting
confidence: 62%
See 1 more Smart Citation
“…Some studies report PDD to be more impaired, 6,7 whereas other studies found no differences. 8,9 Similar inconsistencies have been found when perception of PD patients was compared with healthy controls.…”
Section: Abstract-objectivesupporting
confidence: 62%
“…Some studies report PDD to be more impaired, 6,7 whereas other studies found no differences. 8,9 Similar inconsistencies have been found when perception of PD patients was compared with healthy controls.10 Since operationalized criteria to define the clinical boundaries between PD and PDD or PDD and DLB require refinement, these inconsistencies may be partly due to diagnostic heterogeneity. When DLB was compared with AD, studies consistently reported greater visual impairment in DLB 11 and a recent study found similar impairments in pentagon copying in DLB and PDD.…”
mentioning
confidence: 86%
“…Similarly, executive dysfunction as measured by tasks such as Trails A and B and card sorting are prominent in DLB. 35,36 These features on testing are consistent with the early clinical symptoms reported in fluctuations in alertness. However, orientation has been observed to be relatively preserved in DLB with respect to AD, as memory loss, particularly episodic and recognition memory, may be less severe early on in DLB than AD and PDD.…”
Section: Clinical Coursesupporting
confidence: 71%
“…By contrast, AD patients tend to improve between the drawing and copying portion of the clock task. 35,36 Other areas of cognitive deficit that are more pronounced in DLB than in AD include verbal fluency, psychomotor speed, and executive function. 35 The verbal dysfluency has been found to be more severe in DLB than in AD patients, specifically in letter fluency, whereas in AD letter fluency is relatively intact when compared with category fluency.…”
Section: Clinical Coursementioning
confidence: 99%
“…A recent metaanalytic study by Collerton et al (2003) systematically reviewed 21 studies comparing the cognitive performance of DLB patients; they found that the effect size (Cohen's d: averaged across multiple cognitive domains) was, in fact, larger for DLB (2.0-2.2) than AD (1.4-1.6) patients. Studies comparing AD and DLB patients have pinpointed some differences in cognitive performance: memory impairment is less severe in DLB than AD (e.g., Calderon et al, 2001;Salmon et al, 1996;Shimomura et al, 1998), while visual-perceptual and spatial abilities are more impaired (e.g., Ala et al, 2001;Calderon et al, 2001;Gnanalingham et al, 1997;Salmon et al, 1996). Consistent with the neuropsychological profile, functional imaging studies show that patients with DLB more commonly have reduced perfusion in the occipital lobes than AD patients (Ishii et al, 1999;Lobotesis et al, 2001).…”
Section: Introductionmentioning
confidence: 51%